Analysis of the Notion of Subliminal Techniques Contained in Article 5 of the European Union Artificial Intelligence Regulation (Justicia &Derecho, 2025)
The article examines the notion of subliminal, manipulative or deceptive techniques that are intentionally harmful and significantly and substantially influence the behaviour of individuals or groups of people prohibited in Article 5. 1(a, b and c) of the European Union’s Artificial Intelligence (AI) Regulation and in the Guidelines adopted by the European Commission in 2025 on prohibited practices in the field of AI established by the Regulation. As the Commission’s guidelines point out, subliminal techniques are currently more sophisticated with the use of neurotechnologies such as brain-computer interfaces, where there is a proliferation of cognitive biometric data, without the user’s awareness and sometimes even without their consent, which could cause harm and affect fundamental rights, for example in the area of personal data protection and neurorights, among others. This text also analyses the relationship between the use of AI, neurotechnologies and subliminal techniques that affect the aforementioned rights.
Keywords: AI Act; Subliminal techniques; Neurotechnologies; Mental integrity; Cognitive freedom